Analysis of Production Optimization in Increasing Profits at UD. Tahu Nias - Laoli, Rukun Fataya; Gea, Jeliswan Berkat Iman Jaya; Zebua, Serniati; Gulo, Heniwati (PT. Maju Malaqbi Makkarana, 2025)
Production optimization is a key to increasing efficiency and profitability, especially in businesses such as UD. Tahu Nias in Hiligodu Ombolata Village, Gunungsitoli City, which operates in the tofu production sector. This research is motivated by the production challenges faced by the company, such as limited equipment, late raw material supplies, and an unskilled workforce, which impact the inefficiency of the production process and decrease the level of profitability. The method used in this study is a qualitative descriptive approach with data collection techniques through interviews, observation, and documentation. Informants consisted of the owner, production employees, and other support staff. The results of the study indicate that the production process at UD. Tahu Nias still has manual stages with limited use of machines, especially only at the soybean milling stage. The main obstacles in optimizing production include late raw material supplies, the lack of technology and training for employees. However, the company has made several efforts such as strategic raw material management and efficient division of labor among employees. The conclusion of this study is that production optimization at UD. Nias tofu can be improved through the use of advanced equipment in more modern production facilities, employee skills development through training, and improved production and distribution planning. By implementing these strategies, the company has the potential to sustainably increase operational efficiency and profitability.